Cohesive energy measurement of van der Waals heterostructures by the shaft loaded blister test. (November 2020) - Lou, Liqun; Chen, Peijian; Wang, Zhengjin; Zhang, Shuwen; Gao, Feng
Abstract: To obtain more stable heterostructures and develop the assembly of different 2D materials, precisely evaluation and prediction of interface properties of vdW heterostructures is of essential importance. In the present paper, molecular dynamics simulation and theoretical analysis of the load shaft blister test (SLBT) of vdW heterostructures are conducted. The applied force-debonding radius relation, the relationship between applied force and central deflection, as well as the cohesive energy affected by geometric parameter and experimental setup on the measurement of interface properties are mainly focused. It is found that the SLBT can be well used to measure the cohesive energy of heterostructure materials, and the sample size, the pre-fabricated hole as well as low density defects have ignorable effect on the measurement of cohesive energy. What is more, materials with higher strength should be selected as the upper material to prevent damage of the upper material during loading. The results should be helpful for the measurement of cohesive energy and experimental design of vdW heterostructures at nanoscale.